PERBEDAAN POLA MAKAN SAAT PUASA SUNNAH DENGAN STATUS GIZI DI PONDOK PESANTREN - Amilia Yuni Damayanti; Rochmatul Khamidah Zahro; Fitri Komala Sari (Jurnal Kesehatan Tambusai, 2021)
Background: At this time, Indonesia has 8,1% of adolescents aged 16-18 years with thin and very thin condition. Meanwhile 13,5% of them are having overweight and obesity. The difference of eating patterns while fasting can affect the energy balance and body fat composition and will reduce the amount of nutritional intake that enters into the body. This research was conducted to find out the differences in eating patterns of fasting Daud, Monday – Thursday, not fasting, related to the nutritional status of Boarding School Students. Methods: This study used a cross sectional study. Measurement of eating patterns used a FFQ. The nutritional status based on the value of BMI/age results. The population used were students in the boarding school, aged around 16-18 years. The sampling technique used a quota sampling. Data analysis used Chi-Square, Mann-Whitney, and Kruskal-Wallis Comparative test. Results: The result of this study showed that the majority of Boarding School students had normal nutritional status as much as 84.8% (84 respondents), and they had an adequate of eating pattern as much as 43.4% (43 respondents) of 99 respondents. Conclusion: There was no significant difference in eating patterns of fasting Daud, Monday-Thursday, and not fasting with nutritional status at Boarding School (p=0.280).